Rainfed Farming - M.L. JAT; S.K. Sharma (Ludhiana Kalyani, 2011)
In this book the chapters are devoted mainly in explaining the basic concepts of rainfed farming, meterology, weather data analysis, improving water use efficiency, tillage,watershed management and designing of water harvesting structures.
Rainfall Analysis Rainwater Harvesting Tillage
Keywords: Rainfall Analysis ,Rainwater Harvesting, Tillage